Identification of Blood Circular RNAs as Potential Biomarkers for Acute Ischemic Stroke - Lu, Dan; Ho, Eric S.; Mai, Hongcheng; Zang, Jiankun; Liu, Yanfang; Li, Yufeng; Yang, Bing; Ding, Yan; Tsang, Chi Kwan; Xu, Anding (Frontiers in Neuroscience, 2020)
Many hospitals lack facilities for accurate diagnosis of acute ischemic stroke (AIS). Circular RNA (circRNA) is highly expressed in the brain and is closely associated with stroke. In this study, we examined whether the blood-borne circRNAs can be promising candidates as adjunctive diagnostic biomarkers and their pathophysiological roles after stroke. We profiled the blood circRNA expression in mice subjected to experimental focal cerebral ischemia, and validated the selected circRNAs in AIS patients. We demonstrated that 128, 198 and 789 circRNAs were significantly altered at 5 min, 3 h and 24 h after ischemic stroke, respectively. Our bioinformatic analysis revealed that the circRNA-targeted genes were associated with hippo signaling pathway, extracellular matrix-receptor interaction, and fatty acid metabolism at 5 min, 3 h and 24 h after ischemic stroke, respectively. We verified that many of these circRNAs were conserved in human. Finally, we found that circBBS2 and circPHKA2 were differentially expressed in the blood of AIS patients. These results demonstrate that blood circRNAs may serve as potential biomarkers for AIS diagnosis, and reveal the pathophysiological responses in the brain after ischemic stroke.